Causal relationships between the parameters of gas discharge visualization and leukocytogram - Babelyuk, Valeriy; Tserkovnyuk, Ruslan; Ruzhylo, Sofiya; Dubkova, Galyna; Babelyuk, Nazariy; Zukow, Walery; Popovych, Igor (Journal of Education, Health and Sport, 2021)
Background. Previously we have been shown that between parameters of GDV and principal neuroendocrine factors of adaptation exist strong canonical correlation. In the next study, we detected very strong (R=0,994) integral canonical correlation between the parameters of GDV and Immunity. This study, conducted in the same contingent, will analyze the relationships between GDV parameters, on the one hand, and Phagocytosis and Leukocytogram parameters, on the other. Material and Methods. We observed twice ten women and ten men aged 33-76 years without clinical diagnose. In the morning in basal conditions at first registered kirlianogram by the method of GDV by the device “GDV Chamber” (“Biotechprogress”, SPb, RF). Than we counted up the Leukocytogram and determined Interleukin-1 serum level. Results processed by method of canonical analysis, using the software package “Statistica 5.5”. Results. According to the value of the canonical correlation coefficient R with GDV parameters, the components of the Leukocytogram are arranged in this order: proportion of monocytes (0,769) and eosinophils (0,703), entropy of Leukocytogram (0,636), total leukocytes level (0,558), proportion of lymphocytes (0,492), stub neutrophils (0,374) and polymorphonuclear neutrophils (0,307). Coefficient of canonical correlation between parameters of GDV, on the one hand, and, on the other hand, Leukocytogram, makes 0,904; Leukocytary Strain&Adaptation Indices-1 – 0,756; Leukocytary Strain&Adaptation Indices-2 – 0,783; Interleukin-1 – 0,798. Conclusion. The above data, taken together with the previous ones, state that between parameters of Neuroendocrine-Immune complex and GDV exist strong canonical correlation suggesting suitability of the latter method.